Uncommon Cause of Trigeminal Neuralgia: Tentorial Ossification over Trigeminal Notch - Sun Woo Bang; Kyung Ream Han; Seung Ho Kim; Won Ho Jeong; Eun Jin Kim; Jin Wook Choi; Chan Kim (Case Reports in Anesthesiology)
Ossification of the tentorium cerebelli over the trigeminal notch is rare, but it may cause compression of the trigeminal nerve, leading to trigeminal neuralgia (TN). We were unable to find any previously reported cases with radiological evaluation, although we did find one case with surgically proven ossification of the tentorium cerebelli. Here, we present a case of TN caused by tentorial ossification over the trigeminal notch depicted on magnetic resonance imaging (MRI) and computed tomography (CT).